Leading change step-by-step : tactics, tools, and tales - Spiro, Jody. (San Francisco, CA. : Jossey-Bass, 2011)
A practical, step-by-step guide to leading change efforts for sustainable resultsLeading Change Step-by-Step offers a comprehensive and tactical guide for change leaders. Spiro's approach has been field-tested for more than a decade and proven effective in a wide variety of public sector organizations including K-12 schools, universities, international agencies and non-profits. The book is filled with proven tactics for implementing change successfully, with helpful tools to put change efforts into practice (including forms, rubrics, and helpful questions to ask). Also included are success stories of struggle and success that show how this approach has been used effectively in 22 states and internationally. The tools guide leaders through analyzing situations, identifying stakeholders, and working with them effectively to bring about the desired results -- BACK COVER
Includes index.
Keywords: Educational leadership; Educational change; Educational innovations